2021
DOI: 10.52598/jpll/3/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomizing Students’ Task Engagement in Pair Work in the Language Classroom

Abstract: Student engagement in the second language classroom has been the focus of numerous researchers and teachers. Previous studies have shown that there are several dimensions of student engagement, but it is still unclear how they change (or not) over time and consequently how they affect actual task performance. This study investigated the task engagement of language learners engaged in collaborative writing in pairs. Specifically, it focused on the combination of behavioral, cognitive, emotional, and social dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…All correlations considered, we suggest that a certain level of engagement in one of the dimensions could positively benefit the levels of engagement in the other two. While acknowledging that this is a bold conclusion to draw, these findings go in line with previous research on Engagement with Language that provided support to the dynamic and interrelated nature of the different dimensions (Zhang, 2021;Hiromori, 2021;Toth, 2020;Baralt et al, 2016). Furthermore, the qualitative description of the interactions between participants complements this quantitative analysis and provides further support to the mediating effects and the interrelationship among dimensions.…”
Section: Results and Discussion Related To Research Question 2 And Hy...supporting
confidence: 87%
See 3 more Smart Citations
“…All correlations considered, we suggest that a certain level of engagement in one of the dimensions could positively benefit the levels of engagement in the other two. While acknowledging that this is a bold conclusion to draw, these findings go in line with previous research on Engagement with Language that provided support to the dynamic and interrelated nature of the different dimensions (Zhang, 2021;Hiromori, 2021;Toth, 2020;Baralt et al, 2016). Furthermore, the qualitative description of the interactions between participants complements this quantitative analysis and provides further support to the mediating effects and the interrelationship among dimensions.…”
Section: Results and Discussion Related To Research Question 2 And Hy...supporting
confidence: 87%
“…Similarly, Hiromori (2021) approached engagement in terms of behavioural, cognitive, emotional and social aspects and observed a mutual relationship among these dimensions.…”
Section: Results and Discussion Related To Research Question 2 And Hy...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, research has shown that more motivated learners are likely to learn more than their less motivated counterparts (Hiromori, 2021;Lambert, 2021). There multiple reasons why motivation and the resulting engagement favor learning.…”
Section: Flow and Other Constructs Of Sla Positive Psychologymentioning
confidence: 99%